The social inequalities of Internet access, its use, and the impact on children's academic performance: Evidence from a longitudinal study in Switzerland. (July 2018) - Camerini, Anne-Linda; Schulz, Peter J; Jeannet, Anne-Marie
This longitudinal study explores differences in Internet access and use among school-aged children in Italian-speaking Switzerland and whether and how these differences contribute to inequalities in academic performance. Applying multilevel structural equation modeling with two-wave original survey data from 843 students, their parents, as well as students' end-term school grades, we show that a family's socio-economic status indirectly affects children's school grades as lower parental income leads children to use the Internet more frequently for entertainment and online communication purposes. This form of Internet use also increases as children have more personal digital media devices. As children's increased use of the Internet for entertainment and online communication worsens their academic performance, our results suggest that social inequalities due to children's socio-economic status are reinforced by a second-order digital divide. We discuss potential reasons for our findings as well as their implications and recommendations for possible interventions.